Bohseite, ideally Ca4Be4Si9O24(OH4, from the Piława Górna quarry, the Góry Sowie Block, SW Poland. (2nd January 2018) - Szełęg, E.; Zuzens, B.; Hawthorne, F. C.; Pieczka, A.; Szuszkiewicz, A.; Turniak, K.; Nejbert, K.; Ilnicki, S. S.; Friis, H.; Makovicky, E.; Weller, M. T.; Lemée-Cailleau, M.-H.
Abstract: Bohseite is an orthorhombic calcium beryllium aluminosilicate with variable Al content and an endmember formula Ca4 Be4 Si9 O24 (OH4 ), that was discovered in the Piława Górna quarry in the eastern part of the Góry Sowie Block, ∼50 km southwest of Wrocław, SW Poland. It occurs in a zoned anatectic pegmatite dyke in close association with microcline, Cs-rich beryl, phenakite, helvite, 'lepidolite', probably bertrandite and unidentified Be-containing mica as alteration products after a primary Be mineral, probably beryl. Bohseite forms fan-like or parallel aggregates (up to 0.7 cm) of white, platy crystals (up to 2 mm long) with characteristic striations. It is white with a white streak, is translucent and has a vitreous lustre; it does not fluoresce under ultraviolet light. The cleavage is perfect on {001} and fair on {010}, and neither parting nor twinning was observed. Bohseite is brittle with a splintery fracture and Mohs hardness is 5–6. The calculated density is 2.719 g cm –3 . The indices of refraction are α= 1.579, β = 1.580, γ = 1.597, all ±0.002; 2Vobs = 24(3)°, 2Vcalc = 27°; the optic orientation is as follows: X ^a = 16.1°, Y ^b = 16.1°, Z //c Bohseite shows orthorhombic diffraction symmetry, space group Cmcm, a = 23.204(6), b = 4.9442(9), c = 19.418(6) Å, V = 2227.7(4) Å 3, Z = 4. The crystal structure was refined to an R 1 value of 2.17% based on single-crystal data, and the chemical composition was determined by electron-microprobe analysis. Bohseite is isostructural with bavenite. Bohseite was originally approved with an end-member composition of Ca4 Be3 AlSi9 O25 (OH)3, but subsequent discovery of compositions with Be > 3.0 apfu led to redefinition of its end-member composition, holotype sample and locality, as reported here. There is extensive solid solution in bavenite–bohseite according to the scheme O(2) OH – + T (4) Si 4+ + T (3) Be 2+ ↔ O(2) O 2– + T (4) Al 3+ + T (3) Si 4+, and a general formula for the bavenite–bohseite minerals may be written as Ca4 Bex Si9 Al4–x O28–x (OH)x, where x ranges from 2–4 apfu: Ca4 Be2 Si9 Al2 O26 (OH)2 (bavenite) to Ca4 Be4 Si9 O24 (OH)4 (bohseite).